A forest working plan for the Fort Riley Military Reservation - Yerkes, Guy E. (My University, 1906)
Introduction: The Fort Riley Reservation, composing an area of about 32,000 Acres, is located in Central Kansas. The topography of the land makes it peculiarly well adapted for maneuvers of Cavalry and Field Artillery, the School of Application for these branches of the regular Army being located here. To assist in obscuring the movements of troops, it is proposed to establish belts of trees on the open ridges, particularly those on the North part of the Reserve. Brigadier General E. S. Godfrey, Post Commandant, who is in charge of the work, wishes also to place the woodland of the Reserve under conservative management for the production of fuel, and post and pole timber. The woodland is mostly on the bottom land, and covers about 850 Acres. This working plan provides for the beginning of forestry on the woodland, and for the formation of about fourteen (14) miles of screen -belts. The reservation includes two classes of soil formation - river bottom and upland. Approximately, one-third of the South part of the tract is bottom land, along the Kansas River, which forms part of the boundary of the Reserve. The soil is a fertile sandy loam, formed by alluvial deposits from the river. The sub-soil is coarse sand or gravel. The surface is nearly level, about twelve to sixteen feet above the water table. The greater part of the woodland is on this bottom land. The upland is separated from the river bottom by abrupt rocky slopes, capped with limestone. The surface is rolling or hilly, and is much broken by rocky ravines and gullies. The soil is a clay loam, varying in depth and fertility. The sub-soil is clay or rock. On the ridges, where screen-belts are wanted, no obstruction such as rocks are offered to plowing, and the soil is suitable for tree growth.
Citation: Yerkes, Guy E. A forest working plan for the Fort Riley Military Reservation. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Forestry; Fort Riley Military Reservation; Kansas; Theses